Kolb’s learning Style Affect EFL Creativity of Indonesian Students - Eny Syatriana; Erwin Akib; Saiful Saiful (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to find out the learning preference for English as a Foreign Language learners’ for speaking ability of Muhammadiyah University. Since speaking is the most intense ability to use in communicating with others and it plays very important in a variety of language productions, talks can be in the form of discussion, speech, debate, argumentation, dialogue or conversation, storytelling and retelling. Language users orally use language to express their desires, feelings, thoughts with others, so that people can understand what is expressed. But the fact, the communication still encounters many misunderstandings where the problems may affect the mastery of accuracy, fluency, flexibility and comprehensibility of students. In addition, the role of Kolb learning style to mastering the ability of the students was investigated by fifty eight EFL learners participated in the study. They took a topic to discuss, and engage by an oral interview.In addition, the result of the analysis of the questionnaire significantly predicted that assimilator 44.82% as the abstract conceptualization have and the most cognitive approach is making the biggest contribution compare to other style. This study has focus on need analysis result point out that four types of learning style has significant 0,05 is normal in terms of the learning outcome. These findings provide evidence on the role of Kolb’s learning style can foster the learners’ creative learning in speaking.